An assessment of research and extension by the Department of Fisheries, with emphasis on the needs of small-scale farmers in Northeast Thailand - Supatra Amornchairojkul; Edwards, Peter; Demaine, Harvey; Little, David C.; Overseas Development Administration - UK (Bangkok : Asian Institute of Technology, 1993)
Secondary data on research and current extension projects in Northeast Thailand and field survey data were collected in the study area, Kalasin Province, to assess the effectiveness of the Department of Fisheries' (DOF) research and extension services for farmers. Applied aquaculture research conducted in Northeast Thailand was the responsibility of the Freshwater Fisheries Division. The vast majority was on-station research, although it concerned both high and low-cost technology and also included indigenous wild and economical fish and commonly cultured species. Kalasin Freshwater Fisheries Station was one of five research stations of Khonkaen Freshwater Fisheries Development Center. It was responsible for testing and transferring technology to extension workers and to farmers. At the time of the study, it had one fisheries promotion job and four extension projects planned by the central organization for implementation in the province. They were undertaken by Kalasin Provincial Fisheries Office and/or the Station, Monthly discussions among provincial and district extension workers and researchers were held. Findings from the study area found that both individual and communal extension projects could motivate the farmers to adopt fish culture. However, they were still not so successful in promoting adoption of aquaculture activities of resource-poor farmers. Effectiveness was affected by limited of farm visits in the persuasion period and a shortage of communication media. Therefore, suitable media utilization and trainee-training course should be actively considered. This could be useful for DOF to improve the effectiveness of the {u2022}extension services under conditions of limited government's resources.
A Thesis Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Science, School of Environment, Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 1993
Keywords: Fishery management -- Thailand, Northeastern; Agricultural extension work -- Thailand, Northeastern